Medical reference services quarterly (Haworth Press, 1982)
Quarterly. Intended for medical reference librarians in all settings; will deal with topics of current interest and practical value, as well as research topics and information on online searching. 4 regular sections will be book reviews, online updates, opinions, and user education.